A flexible endoscopic robotic suturing system for gastrointestinal perforations : animal study - Cao, Lin (2020)
Gastrointestinal perforations may be caused due to complicated flexible endoscopic procedures such as Endoscopic Submucosal Dissection (ESD), Endoscopic Full-Thickness Resection (EFTR), and Natural Orifice Transluminal Endoscopic Surgery (NOTES). The most reliable approach of closing gastrointestinal perforations is by suturing which, however, is usually done through open or laparoscopic surgery. Suturing through flexible endoscopic procedures is highly desirable but challenging due to the confined space of the lumen and target area, high dexterity and force demands of suturing tasks, and critical size and strength requirements of the closure. Although two endoscopic defect closure devices exist on the market, i.e., Over-The-Scope Clip (OTSC, Ovesco Endoscopy Inc., Germany) and OverStitich (Apollo Endosurgery Inc., US), both devices are not for standard suturing due to the use of clips or fastening elements, and they are limited with large sizes and the lack of dexterity or tool triangulation. We developed a flexible endoscopic robotic suturing system which can endoscopically close gastrointestinal wounds with standard stitches and knots using a robotic suturing arm (Ø4.4 mm) and a grasping arm (Ø4.2 mm). Both arms are flexible, through-the-scope, and have five Degrees Of Freedom (DOFs). This paper presents an in-vivo test of this system suturing an incision on the rectum wall of a live pig.